“นโยบายเส้นทางสายไหม” กับความสัมพันธ์ทางเศรษฐกิจระหว่างไทย-จีน และแนวโน้มการลงทุนจากญี่ปุ่นในประเทศไทย - วาดีเจริญ, วนิดา (ASIA PARIDARSANA, 2019)
“Silk Road Policy” under the “One Belt One Road” (OBOR) project has been a Chinese national policy initiative, which is a far-sighted vision unveiled by President Xi Jinping – a fifth-generation leader of the Com¬munist Party. China’s national economic development plan No.13 has defined the country’s national economic structure as transforming from a global manufacturing warehouse relying on an export-led strategy to an outward-looking economy – one which goes out to the global market by using “OBOR” strategy. China is currently undertaking the largest project of the century, building a network of railroads and shipping lanes linking itself with 70 countries across Asia, Europe, the Middle East and Africa through funding supported by Asian Development Bank. The purpose of this study is (1) to study the economic relationship between Thailand and China under the Silk Road Policy; and (2) to study Japan’s investment trend in Thailand after the initiative of Silk Road Policy. A qualitative research method was applied, using a secondary data analysis with a focus on the Silk Road Policy as related to Thailand-China economic relationship and Japan’s investment trend. The research result derived from this analysis is being presented in the form of a descriptive summary.